2018
DOI: 10.1186/s12936-018-2229-1
|View full text |Cite
|
Sign up to set email alerts
|

Malaria training for community health workers in the setting of elimination: a qualitative study from China

Abstract: BackgroundContinuous training of health workers is a key intervention to maintain their good performance and keep their vigilance during malaria elimination programmes. However, countries progressing toward malaria elimination have a largely decreased malaria disease burden, less frequent exposure of health workers to malaria patients, and new challenges in the epidemiology of the remaining malaria cases. Moreover, competing health priorities and usually a decline in resources and in political commitment also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…Because of the existence of marketing, China's economy has always grown much stronger in areas of a higher administrative level. In contrast, there is disparity in the availability of health services and significant gaps in awareness of malaria and affordability by inhabitants at different administrative levels to the extent of severity of the illness in malaria patients [16,30]. Therefore, for a number of malaria cases, provincial and municipal healthcare institutions served as their first option because many of them were near cities on their way home, or they lived in cities where better medical care gave them more trust and security.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the existence of marketing, China's economy has always grown much stronger in areas of a higher administrative level. In contrast, there is disparity in the availability of health services and significant gaps in awareness of malaria and affordability by inhabitants at different administrative levels to the extent of severity of the illness in malaria patients [16,30]. Therefore, for a number of malaria cases, provincial and municipal healthcare institutions served as their first option because many of them were near cities on their way home, or they lived in cities where better medical care gave them more trust and security.…”
Section: Discussionmentioning
confidence: 99%
“…In imported malaria cases an extraordinary level of misdiagnosis and severe complications are observed. Poor performance in awareness, attitudes and practices of international labourers from rural areas, low capacity for malaria diagnosis in lower-level administrative healthcare institutions, and infrequency of malaria cases make these challenging characteristics of imported malaria in China [16,20,30]. A critical problem has been observed after a literature review of the challenge to tackle imported malaria in China [30,[34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some CHWs in our study reported experiencing difficulties keeping up with the technical details in the PocketDoktor related to hypertension. Comparable challenges were noted in other studies involving CHWs delivering interventions [39,40]. For example in Nigeria, community extension health care workers (same as CHWs) tasked with delivery of family planning education to communities had limited knowledge of the contraceptives such as emergency contraceptives, intrauterine devices (IUDs) [40].…”
Section: Discussionmentioning
confidence: 95%
“…A PubMed literature search revealed only two studies from the African Region and one study from the Asia and the Pacific Region that have recognized the importance of staff capacity and attitudes together with multi-sectoral collaboration in the malaria elimination scenario [13][14][15].…”
Section: Introductionmentioning
confidence: 99%